The Links between Political Campaigning and Post-Truth - Yaron Katz (Randwick International of Social Science Journal, 2023)
The paper investigates the links between political campaigning and post-truth. The research argues that there are five main factors that make a successful post-truth political campaign. The first is marinating a goal of achieving a practical outcome. The second is the success to control public agenda. The third is providing a different definition of truth. fourth factor is the use of claims based on emotional beliefs. And the fifth is the success to trigger a response from the opposing party. Based on this theoretical approach, the research examines information published in the Israeli election campaign of April 2019 by the leading Likud party and its leader, Prime Minister Benjamin Netanyahu, against their main rivals – Blue and White party and its leader, Benny Gantz - former Israel Defense Forces (IDF) Chief of Staff. The issue examined is the post-truth campaign involving the cell phone hacking of Gantz. The examination looks at the campaign according to the main factors that make a successful post-truth political campaign, as described earlier. It aims to examine the way that these factors were implemented by the Likud campaign – and conclude if using these factors was properly done in this post-truth campaign.